2017
DOI: 10.1177/0170840616685355
|View full text |Cite
|
Sign up to set email alerts
|

Sober Intoxication: Institutional Contradictions and Identity Work in the Everyday Life of Four Religious Communities in Italy

Abstract: This study explores how organization members manage institutional contradictions in their everyday life without aiming at change-oriented agency. Drawing on interviews, observations, and archival data from four religious communities in Italy, we find that when organization members experience institutional contradictions between two logics that provide conflicting identity prescriptions but to which they are emotionally attached, they engage in identity work that helps them ameliorate-but not eliminate-tensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 66 publications
(129 reference statements)
1
30
0
Order By: Relevance
“…Dutton et al () argued the more an individual's overall identity structure contains complex facets (as in the case of many religious and occupational identities), the more that individual has the capacity to form positive relationships with diverse others at work. One way of dealing with contradictions between personal identities and organizational practice is to engage in identity negotiation in order to temporarily resolve tensions when identities are incongruent (Giorgi & Palmisano, ). Yet, the ongoing experience of identity conflict might ultimately prompt resolution via institutional or individual change (Giorgi & Palmisano, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dutton et al () argued the more an individual's overall identity structure contains complex facets (as in the case of many religious and occupational identities), the more that individual has the capacity to form positive relationships with diverse others at work. One way of dealing with contradictions between personal identities and organizational practice is to engage in identity negotiation in order to temporarily resolve tensions when identities are incongruent (Giorgi & Palmisano, ). Yet, the ongoing experience of identity conflict might ultimately prompt resolution via institutional or individual change (Giorgi & Palmisano, ).…”
Section: Discussionmentioning
confidence: 99%
“…One way of dealing with contradictions between personal identities and organizational practice is to engage in identity negotiation in order to temporarily resolve tensions when identities are incongruent (Giorgi & Palmisano, ). Yet, the ongoing experience of identity conflict might ultimately prompt resolution via institutional or individual change (Giorgi & Palmisano, ). However, identity states (high congruence, coexistence, or incongruence) affect not only employees as individuals but also their relationships at work.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown how organizational identification can be constructed through the consumption of particular kinds of food (Kenny ), prayer (Gutierrez et al . ; Giorgi and Palmisano ), collaboration in formal research projects (Davenport and Daellenbach ), and ‘voluntary’ subordination and obedience (Karreman and Alvesson ). Anteby (2010) describes how craftsmen at AeroDyn enacted their identification with particular occupations (e.g.…”
Section: Approaches To Identity Work and Identificationmentioning
confidence: 99%
“…To this end, we combine insights from organizational institutionalism and network studies to develop a communal perspective on favoritism. Insights from organizational institutionalism are helpful because this strand of institutional theory is sensitive to the fact that the behaviors of individuals are subject to broader societal and communal norms, as well as the fact that these may pose conflicting demands (e.g., Currie and Spyridonidis 2016;Giorgi and Palmisano 2017;Pache and Santos 2013;Smets et al 2015;Thornton et al 2012). Specifically, we first draw on insights from organizational institutionalism regarding institutional logics and social cues (DiMaggio 1997;Thornton et al 2012;Weber and Glynn 2006) to develop theory about when and how recruiting managers experience communal norms towards favoritism during recruitment and selection processes.…”
Section: Towards a Communal Perspective On Favoritismmentioning
confidence: 99%